A Systematic Literature Review of Six Sigma Implementation in Services Industries - Utomo Utomo (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2020)
Six Sigma has received a lot of attention in the industrial sector from the manufacturing industry to the service industry. More in-depth knowledge of Six Sigma has been overgrowing. Many pieces of training and researches on Six Sigma conducted in industries and universities. This literature review aims to present an overview of the implementation of Six Sigma in the service industry. Besides, it can also be useful to obtain information about the benefits achieved, the main difficulties encountered, and lessons that can be taken in the implementation of Six Sigma. Hopefully, this finding will be useful for other service organizations that wish to implement Six Sigma. The Six Sigma method that has long been introduced and implemented is DMAIC (Determine, Measure, Analyze, Improve, and Control).